Penerapan Media Pembelajaran Google Sites Materi Sistem Pencernaan Manusia untuk Meningkatkan Hasil Belajar Siswa Kelas 5 Sekolah Dasar - Aulia Fitri Syalsabillah (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2024)
This research aims to evaluate the effectiveness of implementing Google Site as a learning media in enhancing students' learning outcomes in a specific subject. Against the backdrop of rapid technological advancement, the integration of technology in education is crucial to improve the quality of education. The research method employed is classroom action research with two cycles, where observations of teacher and student activities and evaluations of student learning outcomes were conducted in each cycle. The research findings indicate a significant improvement in student learning outcomes following the implementation of Google Site as a learning media. The average student grades increased from 75 in cycle I to 90 in cycle II, with all students achieving a "very good" criteria. The implications of this research underscore the importance of utilizing technology in the learning process to achieve optimal learning outcomes.